Beragama dan Berakal Sehat - Fidelis Den (STIPAS St. Sirilus Ruteng, 2020)
Religion (God) has been the inspiration for irrational acts, violence, and cruelty to fellow human beings. For God’s sake, religious people easily sacrifice themselves and others and thus they do not respect the dignity of human beings. These things according to Feuerbach are nonsense. According to him, God, religion and humans must be understood in one unified whole. Human dignity must be respected in the context of a very intimate relationship with God and with others. That’s what makes sense. Common sense is actually a very important part of living a religious life. Only common sense can relive brutality in the name of God and religion and return religion to its spirit as an inspiration for peace by giving priority to respect for human dignity.